Thucydides on international law and political theory - Kareklas, Iakōvos, 1976- (Lexington Books, 2020)
"This book of Thucydidean scholarship demonstrates that international law existed in systematic form in classical Greece. Apart from comprising a philological analysis of some pivotal aspects of the history of the Peloponnesian War, the author argues that the work of Thucydides has greatly influenced contemporary international law and politics"--